Melting and Exhumation of the upper structural levels of the Greater Himalaya Sequence and Makalu granite: constraints from thermobarometry, metamorphic modeling and U-Pb geochronology - Streule, Michael J; Searle, Michael P; Horstwood, Matthew SA; Waters, David (Himalayan Journal of Sciences, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> DOI = 10.3126/hjs.v5i7.1339 Himalayan Journal of Sciences Vol.5(7) (Special Issue) 2008 p.162